Pneumococcal Carriage Recovered from Healthy Children and Their Possible Association with Some Risk Factors in Outpatient Department of a 1000 bedded Tertiary Care Hospital at Dhaka City - Shormin, Moonmoon; Shamsuzzaman, SM; Mondol, Md Eunus Ali; Afroz, Samira; Rashed, Asif (Bangladesh Journal of Infectious Diseases, 2020)
Background: Detection and monitoring of nasopharyngeal carriage of Streptococcus pneumoniae is important to assess the impact and effectiveness of pneumococcal vaccine programs. Objective: The aims of this study were to assess the nasopharyngeal colonization rate, investigate some of the risk factors for nasopharyngeal colonization with S. pneumoniae from healthy children. Methodology: The study was conducted in the department of microbiology of Dhaka Medical College Hospital (DMCH). Data were collected among 200 under five healthy children in different age group (13 months to 36 months), from different socioeconomic status with cramped housing condition from Pediatric OPD of Dhaka Medical College Hospital. S. pneumoniae were isolated and identified by culture, Gram staining, biochemical test and polymerase chain reaction (PCR). Result: Out of 200 nasopharyngeal swabs, 67 (33.50%) were found to be carriers positive by culture and 92(46%) by PCR. The carrier rate was higher among 13 months to 36 months, low and middle socio-economic groups and among with cramped housing condition. Conclusion: In conclusion various factors may affect the nasopharyngeal colonization with S. pneumoniae including early age of life, different socio-economic and living condition. Bangladesh Journal of Infectious Diseases 2019;6(2):48-52